Evaluating the effect of alternative neutralising agent and seeding on the zinc recovery through the Zincor iron removal circuit - Taggart, Diane (Department of Chemical Engineering, 2016)
Zincor's average zinc recovery was 90.29 % (for the period of 1 January 2009 to 30 September 2011), which was well below the industry standard of 96 %. Due to limitations in Zincor's iron removal technology, the maximum achievable recovery was 94 %. The zinc loss through the iron residue was the second biggest contributor to the overall zinc losses, so that there was much room for improvement. The calcine used for neutralisation in the Iron Removal Stage contained a portion of insoluble zinc ferrite. The insoluble zinc loss through the iron residue was associated with the presence of the insoluble zinc ferrite, as well as the phenomenon of coating of unleached neutralising agent by iron precipitate. The soluble zinc loss was a function of the dewatering characteristics of the precipitate. The work included the evaluation of alternative neutralising agents to supplement or replace calcine, as well as the implementation of a seed recycle. A review of literature found that the use of an alternative neutralising agent that contained little or no zinc could potentially reduce the insoluble portion of the zinc loss. Secondly, the presence of seed could potentially reduce both the soluble and insoluble zinc losses by promoting agglomeration growth and providing additional surface area for precipitation to occur (thereby reducing coating of zinc-rich neutralising agents). The laboratory work evaluated a number of alternative neutralising agents, but focused on the use of DRC oxide and limestone for neutralisation. These were evaluated separately and in combination, with and without a seed recycle.